2011
DOI: 10.1017/s0959270910000584
|View full text |Cite
|
Sign up to set email alerts
|

Effects of grassland burning on reproductive success of globally threatened Strange-tailed Tyrants Alectrurus risora

Abstract: SummaryThe north-east of Argentina contains a high number of globally threatened grassland birds and is increasingly managed for livestock, with annual burning in remaining natural grasslands. The Strange-tailed Tyrant Alectrurus risora, a globally threatened grassland specialist, has suffered a 90% contraction in its original range. From 1996 to 2008 we monitored a breeding population in Formosa, north-east Argentina, and explored the effect on breeding of four accidental and one prescribed fires. The plant m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 23 publications
1
13
0
4
Order By: Relevance
“…Indeed, Neotropical ornithology has blossomed even in countries (e.g., Ecuador) fauna such as the USA and Argentina. Common and broadly distributed species are usually better known, with a few notable exceptions where a species has been targeted by particular research teams (e.g., Alectrurus risora, di Giacomo et al 2011). Our results are consistent with earlier findings, in which geographic ranges and abundance explain over 60% and 30%, respectively, of the variance of discovery dates of oscine passerine birds (Blackburn & Gaston 1995).…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, Neotropical ornithology has blossomed even in countries (e.g., Ecuador) fauna such as the USA and Argentina. Common and broadly distributed species are usually better known, with a few notable exceptions where a species has been targeted by particular research teams (e.g., Alectrurus risora, di Giacomo et al 2011). Our results are consistent with earlier findings, in which geographic ranges and abundance explain over 60% and 30%, respectively, of the variance of discovery dates of oscine passerine birds (Blackburn & Gaston 1995).…”
Section: Discussionsupporting
confidence: 91%
“…Most studies on direct effects of fires are on mammals or birds (Lyon et al, 2000) and found negligible mortality of mediumand large-bodied mammals (Singer et al, 1989;Prada and Marinho, 2004) and little mortality of adult birds (Finch et al, 1997;Di Giacomo et al, 2011). Small mammal populations may experience a reduction in abundance immediately after the fire (Simons, 1991;Schwilk and Keeley, 1998;Lyon et al, 2000), with rapid recovery (Henriques et al, 2000;Briani et al, 2004;Henriques et al, 2006), which may result in increased abundance and diversity (Vieira, 1999).…”
mentioning
confidence: 99%
“…Malan 1998;Jansen et al 1999) and potential mechanisms for population decline. On the southern edge of the tropics in Argentina, extensive and frequent savanna fires affected the settlement rates, and therefore the breeding success, of female Strange-tailed Tyrants (Alectrurus risora), which prefer unburnt savanna vegetation as nesting sites (Di Giacomo et al 2011), whereas fire suppression may lead to vegetation thickening and loss of preferred nesting habitat. The study thus mirrors the case of the Red-backed Fairy-wren in Australian savannas , and reiterates that nuances in the spatio-temporal patterning of savanna fires may interact with the ecologies of species to affect population trajectories.…”
Section: Tropical Savannas On Other Continentsmentioning
confidence: 99%
“…This may be best addressed with focussed studies on how the behaviour, breeding success, movements and survival of individuals of exemplar species are affected by different fire-pattern attributes (e.g. Di Giacomo et al 2011) and extrapolative modelling of results from such studies.…”
Section: Are There Ideal or Threshold Landscape Mosaics Relating To mentioning
confidence: 99%